KOMPETENSI PENYULUH PERTANIAN LAPANGAN (PPL) DALAM DIFUSI INOVASI BUDIDAYA PADI ORGANIK PADA MASYARAKAT PETANI (KASUS DI KELURAHAN FAJAR ESUK, KECAMATAN PRINGSEWU, KABUPATEN PRINGSEWU) - Nadia Azzahra; Tubagus Hasanudin; Suarno Sadar (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to find out the extension worker competencies of organic rice innovation, the level of diffusion of the innovation, and factors related to the diffusion in farmer society in Fajar Esuk Urban Village Pringsewu Subdistrict.  The location of this study was chosen purposively in Fajar Esuk Urban Village with 11 respondents.  Data of this research were collected in August 2017 with  a survey method.  The research used descriptive analysis and nonparametric statistic Rank Spearman correlation test.  The results of this research showed that the extension worker competencies on diffusion of organic rice cultivation innovation in farmer society is quite competent (middle class).  The level of diffusion innovation of organic rice cultivation is in a medium class.  Innovation characteristics variable (X2) has a significant correlation with diffusion of organic rice cultivation.  However, the extension worker competencies(X1), society support (X3) and farmer’s perception about organic rice cultivation (X4) have no significant correlation with diffusion organic rice cultivation innovation in farmer society.Key words :competence, cultivation, diffusion, innovation, organic rice